Chapter 26 Interaction in Aerial Warfare The Role of the Mission Commander in Composite Air Operations (COMAO) - Fredriksen , Pål Kristian (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"This chapter explores the leadership practices of Mission Commanders. The major focus is on key features in leadership practices that contribute to effective samhandling in the execution of Composite Air Operations and handling of unexpected events. "Aerial warfare" is the term used to describe the use of military aircraft and other aeronautical equipment in warfare. Air power has become the preferred instrument for politicians and commanders to achieve strategic and operational objectives across a spectrum of conflicts, ranging from humanitarian aid to combat action. Air campaigns like OD/UP and MINUSMA are conducted through a series of parallel and sequential Composite Air Operations (COMAO). COMAO is the term used when dissimilar types of aircraft interact in coordinated actions to achieve defined military objectives within a given time and geographical area. The study indicates that joint practice and a joint process for learning and leadership play vital roles in the successful conduct of COMAO in war. Joint practice during exercises like RED FLAG provides the opportunity to develop the interactional skills that are needed in modern aerial warfare. Important principles in joint practice are that you train as you fight, you experience a progression in challenge and that all participants participate in the exchange of ideas and lessons learned."